Perbedaan Rerata Tekanan Darah pada Penderita Hipertensi Derajat I (Satu) Wanita Usia Reproduktif dengan Pemberian Jus Wortel (Daucus Carota L) di Wilayah Kerja Puskesmas Tigo Baleh Kota Bukittinggi - Kartika Mariyona; Pagdya Haninda Nusantri Rusdi; Lastri Oktari Tanjung (Universitas Batanghari Jambi, 2022)
Hypertension is a condition without symptoms, where abnormally high blood pressure in the arteries causes an increased risk of stroke, aneurysm, heart failure, heart attack and kidney damage and an increase in systolic blood pressure of at least 140 mmHg or diastolic blood pressure of at least 90 mmHg. the main cause of hypertension in Indonesia, this disease is a very common intervention a person will say hypertension if he has systolic blood pressure ≥ 140 mmHg and diatolic blood pressure ≥ 90 mmHg, systolic blood pressure is the main measurement which is the basis for determining hypertension. This research was conducted in the Tigo Baleh Health Center in Bukittinggi City. The research design was Quasi experiment sample of 10 people with hypertension (I) of reproductive age women using two groups of pre-test and post-test subjects were divided into 2 groups, control and intervention groups . The intervention group was given 200 grams of carrot juice which was processed into juice for 5 consecutive days of data analysis using a t-dependent statistical test. Average pre-test blood pressure 147 / 90.0 mmHg (control) and 141 / 84.5 mmHg (intervention), and post-test average blood pressure 146 / 89.4 mmHg (control) and 130/80 6 mmHg (intervention). Difference in average blood pressure before and after administration of carrot juice is 1.32 / 0.68 mmHg (control) and 10.6 / 3.96 mmHg (intervention). The results of the statistical test found that there was an effect of carrot juice administration on changes in blood pressure in patients with first-degree hypertension in women of reproductive age where the p-value was 0.09 / 0.43. The conclusion of this study is that the administration of carrot juice can reduce blood pressure in patients with hypertension degree I (one) women of reproductive age, henceforth it is recommended for patients with hypertension to use carrot juice as an alternative non-pharmacological treatment..